Negative health care experiences of immigrant patients: a qualitative study - Suurmond, Jeanine; Uiters, Ellen; de Bruijne, Martine C; Stronks, Karien; Essink-Bot, Marie-Louise (BMC health services research, 2011)
Background Negative events are abusive, potentially dangerous or life-threatening health care events, as perceived by the patient. Patients' perceptions of negative events are regarded as a potentially important source of information about the quality of health care. We explored negative events in hospital care as perceived by immigrant patients. Methods Semi-structured individual and group interviews were conducted with respondents about negative experiences of health care. Interviews were transcribed and analyzed using a framework method. A total of 22 respondents representing 7 non-Dutch ethnic origins were interviewed; each respondent reported a negative event in hospital care or treatment. Results Respondents reported negative events in relation to: 1) inadequate information exchange with care providers; 2) different expectations between respondents and care providers about medical procedures; 3) experienced prejudicial behavior on the part of care providers. Conclusions We identified three key situations in which negative events were experienced by immigrant patients. Exploring negative events from the immigrant patient perspective offers important information to help improve health care. Our results indicate that care providers need to be trained in adequately exchanging information with the immigrant patient and finding out specific patient needs and perspectives on illness and treatment.